2015
DOI: 10.1007/s00264-015-2668-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tibial bone loss in antegrade versus retrograde tunnel placement for anterior cruciate ligament reconstruction

Abstract: Compared with conventional techniques, all-inside retrograde drilling of tibial bone sockets is effective in preserving significant bone stock, which might be beneficial for revision reconstruction in cases of eventual primary graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Studies using X-ray and CT imaging to evaluate the sockets drilled with an all-inside ACL technique have reported less socket expansion and preserved bone stock compared to full tunnels seen in standard ACL techniques. 27,28 The importance of this is most evident when drilling the tibial socket for the all-inside ACL suspensory fixation since this can reduce tibial microfracture trauma that is seen with full tunnel tibial drilling in standard ACL techniques. 29 Also, when closedsockets are created, there will be less graft length available for the windshield-wiper and bungee cord phenomena compared to full tunnels.…”
Section: Sockets Versus Tunnelsmentioning
confidence: 99%
“…Studies using X-ray and CT imaging to evaluate the sockets drilled with an all-inside ACL technique have reported less socket expansion and preserved bone stock compared to full tunnels seen in standard ACL techniques. 27,28 The importance of this is most evident when drilling the tibial socket for the all-inside ACL suspensory fixation since this can reduce tibial microfracture trauma that is seen with full tunnel tibial drilling in standard ACL techniques. 29 Also, when closedsockets are created, there will be less graft length available for the windshield-wiper and bungee cord phenomena compared to full tunnels.…”
Section: Sockets Versus Tunnelsmentioning
confidence: 99%
“…There is concern about the windshield wiper and bungee cord phenomenon that may occur with suspensory fixation. Prior studies evaluating sockets drilled with an all-inside ACL technique have revealed less socket expansion and preserved bone stock compared to full tunnels seen in standard ACL techniques on x-ray and CT scans [ 90 , 91 ]. This is extremely crucial when drilling the tibial socket for all-inside ACL suspensory fixation because it reduces the risk of tibial microfracture trauma seen with full tunnel tibial drilling in standard ACL techniques [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…By short graft we signify the introduction of a minimum and adequate collagen tissue bundle being press fit into a limited socket in the epiphysis at the anatomic footprints of the native ACL to obtain a primary fixation and healing of the ligament. The rationale of its uses relies on the following substantial benefits as shown by Colette and Cassard: 27 bone tissue 28 and ligament sparing is of particular importance in a paediatric setting, 29 tensile strength resistance, low elongation rate when preconditioned, high stiffness and fixation with a tight 360° bone to graft contact.…”
Section: Discussionmentioning
confidence: 99%